Enhanced photodynamic therapy by encapsulation of perfluorocarbon into PEGylated near-infared dyes - Jiang, Ke; Wang, Haoran; Zhang, Huanhuan; Hu, Yiqiao; Wu, Jinhui (Cellular and Molecular Biology, 2018)
Near-Infrared (NIR) dyes, with improved tissue penetration, minimal invasiveness and high specificity, have gained great interests in diagnosing and treating tumors. However, the poor solubility in aqueous medium and low 1O2 quantum yields of NIR dyes restrict their application in PDT (photodynamic therapy) research. Herein, a novel nanosystem with modifying the NIR dyes and encapsulating perfluorocarbon is reported for improving the PDT effectiveness of NIR dyes. By adding the PEG2000-SH and the C13 carbon chain to a NIR representative dye IR780, the new formed material PEG-IR780-C13 shows good solubility in water. Then PFTBA was encapsulated into PEG-IR780-C13 to form a nanosystem (PFTBA@PEG-IR780-C13). When exposed to laser irradiation, the nanosystem showed enhanced production of 1O2 and significantly increased PDT both in vivo and in vitro. Therefore, this work provides an approach for design and application of NIR dyes.